Answer:
The function is [tex]P(x) = \frac{1}{2} e^{-x^2} +0.016[/tex]
Step-by-step explanation:
From the question we are told that
The rate of growth is [tex]P'(x) = xe^{x} - x^2[/tex]
The total profit is [tex]P(2) =[/tex]$25,000
The time taken to make the profit is [tex]x = 2 \ years[/tex]
From the question
[tex]P'(x) = xe^{-x^2}[/tex] is the rate of growth
Now here x represent the time taken
Now the total profit is mathematically represented as
[tex]P(x) = \int\limits {P'(x)} \, = \int\limits {xe^{-x^2}} \,[/tex]
So using substitution method
We have that
[tex]u = - x^2[/tex]
[tex]du = 2xdx[/tex]
So
[tex]p(x) = \int\limits {\frac{1}{2} e^{-u}} \, du[/tex]
[tex]p(x) = {\frac{1}{2} [ e^{-u}} +c ][/tex]
[tex]p(x) = {\frac{1}{2} e^{-x^2}} + \frac{1}{2} c[/tex] recall [tex]u = - x^2[/tex] and let [tex]\frac{1}{2} c = Z[/tex]
At x = 2 years
[tex]P(x) =[/tex]$25,000
So
Since the profit rate is in million
[tex]P(x) =[/tex]$25,000 = [tex]\frac{25000}{1000000} =[/tex]$0.025 millon dollars
So
[tex]0.025 = {\frac{1}{2} e^{-2^2}} + Z[/tex]
=> [tex]Z = 0.025 - {\frac{1}{2} e^{-2^2}}[/tex]
[tex]Z = 0.016[/tex]
So the profit function becomes
[tex]P(x) = \frac{1}{2} e^{-x^2} +0.016[/tex]